SURGEONS BEHAVIOR TOWARD PROPHYLAXIS ANTIBIOTICS IN SANGLAH HOSPITAL - Suranadi, I Wayan; Sukrama, Dewa Made; Budayanti, Ni Nyoman Sri; Pradhana, Adinda Putra; Amin, Yusuf Sidang (DiscoverSys Inc., 2018)
Â Background: The emergence of antibiotic resistance is a complicated problem due to many factors, especially its use and abuse. Inappropriate use of antibiotics is very common in both developed and developing countries. The goal of this study was to see the knowledge of the surgeons toward prophylaxis antibiotic at Sanglah Hospital.Methods: This is a descriptive study of 55 surgeons who performed elective surgery at Sanglah Hospital. A questionnaire was filled by the surgeons randomly without prior notice about the study. The information about their behavior toward prophylaxis antibiotics was gathered from medical record of the day.Result: Out of the 55 surgeons participated in this study, 85.5% have followed a training on rational antibiotic use. The level of knowledge about factors that can increase surgical wound infections is quite good (94.4%), while the knowledge regarding factors that can reduce surgical wound infections very low (16.4%). Almost all (92.7%) clean-surgery patients were given prophylactic antibiotics. The most given antibiotic was ceftriaxone (72.7%), the third generation of cephalosporins.Conclusion: The mean knowledge of the surgeons toward antibiotic prophylaxis was 59.8%. The most used antibiotic as pre-surgical prophylaxis was ceftriaxone. And the time of administration for prophylaxis antibiotic was 16-60 minutes prior to surgical incision.